Embracing Educational Modernisation In Mercosur: An Institutional Analysis Of Argentina's Integration Of Infrastructure And Human Capital | Abraçando A Modernização Educacional No Mercosul: Uma Análise Institucional Da Integração Da Infraestrutura E Do Capital Humano Na Argentina - Facundo Guadagno (Revista Neiba, Cadernos Argentina Brasil, 2024)
ABSTRACT This paper examines how Argentina has integrated its infrastructure and human capital into educational modernisation. It explores whether collaborations with other regional countries have existed and their impact. The central question is: How is Argentina embracing new technologies in education? Using an institutional approach, the paper highlights that incentives are one of the main challenges to improving Argentina's educational position. Data from the country's latest census, the Aprender educational test, PISA, and specialised literature are utilised to add robustness to the investigation. The prognosis is adverse; in most provinces, students lack access to essential services and adequate technological devices, leading to difficulties in understanding basic texts or performing simple calculations. Economic stagnation and increasing poverty exacerbate the situation, with educational institutions focused on retaining students rather than promoting academic content. The paper also considers how collaboration with Mercosur countries might alleviate the problem under optimal conditions. Keywords: Comparative politics; regionalismo; education. ---- RESUMO Neste artigo, examinamos como a Argentina integrou sua infraestrutura e capital humano na modernização da educação. Consideramos a existência de colaborações com outros países da região e seu impacto. A pergunta central é: como a Argentina está adotando novas tecnologias na educação? Usando uma abordagem institucional, destacamos que a falta de incentivos é um dos principais desafios para melhorar a posição educacional da Argentina. Dados do último censo do país, o teste educacional Aprender, PISA e literatura especializada são utilizados para agregar robustez à investigação. O prognóstico é negativo; na maioria das províncias, os alunos carecem de acesso a serviços essenciais e dispositivos tecnológicos adequados, resultando em dificuldades para entender textos básicos ou realizar cálculos simples. A estagnação econômica e a crescente pobreza agravam a situação, com instituições educacionais focadas em reter alunos em vez de promover conteúdo acadêmico. O artigo também considera como a colaboração com países do Mercosul pode aliviar o problema em condições ótimas. Palavras-chave: Política comparada; regionalismo; educação.